Advances in Metal-Catalyzed Cross-Coupling Reactions of Halogenated Quinazolinones and Their Quinazoline Derivatives - Mphahlele, Malose Jack (Molecules, 2014)
Halogenated quinazolinones and quinazolines are versatile synthetic intermediates for the metal-catalyzed carbon–carbon bond formation reactions such as the Kumada, Stille, Negishi, Sonogashira, Suzuki-Miyaura and Heck cross-coupling reactions or carbon-heteroatom bond formation via the Buchwald-Hartwig cross-coupling to yield novel polysubstituted derivatives. This review presents an overview of the application of these methods on halogenated quinazolin-4-ones and their quinazolines to generate novel polysubstituted derivatives.